Additions to the bivalve fauna of the Peruvian sea - Paredes, Carlos (2012)
The following species of Bivalvia are recorded for the first time for Peruvian sea: Ennucula panamina (Dall, 1908), Nuculana (Nuculana) loshka, (Dall,1908), Saccella laeviradius (Pilsbry & Lowe, 1932), Liralucina approximata (Dall, 1901), Carditamera radiata (G. B. Sowerby I, 1833), Carditella (Carditella) naviformis (Reeve, 1843); Macoma (Psammacoma) elytrum Keen, 1958, Psammotreta (Psammotreta) pura (Gould, 1853), Sphenia fragilis (H. Adams & A. Adams, 1854) y Caryocorbula amethystina Olsson, 1961. Se informa sobre la distribución, el hábitat y comentarios relevantes sobre cada una de las especies.